Study of Natural and Accelerated Weathering on Mechanical Properties of Antioxidants Modified Low Density Polyethylene Films for Greenhouse - Othman Al Othman; Shan Faiz; Muhammad Abduh Tuasikal (International Journal of Polymer Science)
Natural and accelerated weatherings were studied to inspect the effect of antioxidants to protect low-density polyethylene (LDPE) films for commercial application as greenhouse covering materials in Saudi Arabia. In this investigation, six different formulations of LDPE film with incorporation of antioxidants were prepared and compared with neat LDPE. The samples were extruded and blown into a film using twin-screw extruder and film blowing machine. The LDPE films were exposed for outdoor weathering in Riyadh during the period of 90 days (mid of June to mid of September) while the accelerated tests were performed by Weather-Ometer. The film having 0.2 wt% Alkanox-240 (AN-0.2) stabilizers showed the highest tensile strength among all samples during natural and 100-hour accelerated weathering (10.9 MPa and 21.8 MPa, resp.). The best elongation at break was witnessed in 0.2% Good-rite antioxidants which were 64% in natural weathering; however, 0.5% Good-rite antioxidants showed 232% in accelerated weathering. The film having 0.5 wt% Good-rite 3114 (GR-0.5) antioxidant could withstand 70 days during natural exposure before the tensile strength values were reduced to 2/3rd of the initial. The present study suggested that the addition of antioxidants Good-rite, Anox, and Alkanox can improve the mechanical strength, film’s life, effectiveness, and stability and they are suitable to be incorporated in LDPE for commercial greenhouse films.